Analisis Determinan Kreativitas Aparat Pengawas Internal Pemerintah (APIP) (Studi Kasus di Inspektorat Kabupaten Wonosobo) - Kurniawati Mutmainah (Journal of Economic, Management, Accounting and Technology (JEMATech), 2019)
This study aims to examine the influence of internal factors for the creativity Government Internal Supervisory Apparatus. Population in this studi is all emplyoeed at Inspektorat of Wonosobo. The number of sample is 30 respondents, the sampling technique in this study was conducted by purposive sampling method. The sample was an auditor and internal supervisory who works in the Inspektorat of Wonosobo. Data were collected through questionnaires and analyzed method used in this study is multiple linear regression whit the help of SPSS statistic v.22 software. The result of this study indicate that intellectual and idealism have a positive effect on the creativity of Government Internal Supervisory Apparatus. While the gender, job tenure, relativism and motivation have no effect on the creativity of Government Internal Supervisory Apparatus